The effect of job stressor on stress on the employees of logistics firms in Kota Kinabalu with the moderating effect of personality and stress coping strategy - Muhammad Naseef Abdul Majeed Farooq (2012)
This is a research undertaken to study the level of stress which affects employees of logistics firms in Kata Kinabalu. On the other the hand the Job stressor is the independent variable which relates to stress whereby this study is one of a kind because the industry chosen has never been researched anytime in the near past and present. The job stressors consist of three components: individual stressor, organizational stressor and non-organizational stressor which are moderated by Personality and Stress Coping Strategy. The research was performed successfully which proved there is significant relationship between Job stressor and Stress though there was no significance between stress coping and stress. The study is just an eye opener for other researchers to do further research on the logistics firms all over Sabah whereby this one industry which has been ignored in Sabah.